Genetic diversity near the DGAT1-2 gene for high oleic acid content and kernel trait variation in a maize breeding collection - Olmos, Sofía Eugenia; Trejo, J.M.; Percibaldi, Nora Mabel; Eyherabide, Guillermo (2018)
Previous studies in maize have identified three quantitative trait loci (QTLs) coding for high oleic acid content (HOAC) (QTLs oleic6-1, oleic6-2, and oleic6-3) at bins 6.04–6.05, proximal to the DGAT1-2 gene. The aims of this work were (i) to discover new markers for linkage disequilibrium (LD) and haplotype analysis distal to DGAT1-2, (ii) to develop a new DGAT1-2 PCR probe to detect the allele determining HOAC (F469 insertion), (iii) to conduct cluster analysis for kernel traits, and (iv) to assess genetic diversity, LD, and association analysis for kernel traits with the DGAT1-2 PCR probe and 13 markers previously mapped near DGAT1-2 in the Argentine temperate maize collection of 111 inbred lines. The results showed high haplotype diversity distal to DGAT1-2 and relatedness between the inbred line LP199 (with HOAC) and the Non-Stiff Stalk line W22 (reference genome). The frequency of F469 was low (20%). F469 was clustered with flint-grain type characteristics, whereas HOAC was associated with F469 across linear models. Genetic diversity at bins 6.04–6.05 was high (0.62), whereas LD extent was low (r2 ≤ 0.45). This low extent of LD indicates a high level of recombination and no LD between DGAT1-2 and markers flanking QTLs oleic6-1 to 3. Nevertheless, the significant LD between markers flanking those QTLs and the cosegregation of F469 with nc009 (markers flanking QTLs oleic6-1 and 2) during inbred line conversion suggest that these QTLs might contribute to HOAC in the breeding collection. However, further studies are needed to precise mapping at bins 6.04–6.05 for breeding purposes.